O terrário como prática pedagógica: promovendo a educação ambiental crítica na educação infantil - Oliveira, Márcia de Souza (2024)
The school is a place of learning and construction of knowledge; therefore, discussing the theme of environmental education in different teaching modalities is crucial for developing the critical thinking of the subjects involved in this process. The terrarium is a practice that aids in children’s education and contributes to sustainable development. This research aimed to investigate the process of continuing education for teachers and its relationship with the teaching of Critical Environmental Education and Scientific Literacy in Early Childhood Education, using the terrarium as a practical environmental activity. The methodology employed was a qualitative approach and a case study involving the construction of a terrarium as a practical experiment. The subjects of the process were teachers working in Early Childhood Education and PreSchool from two municipal schools in the city of Cachoeiro de Itapemirim, and their respective schoolchildren. The research was conducted between August and November 2023, totaling ten meetings. The following data collection instruments were used in the study: document analysis, observation of daily school activities, questionnaires, field diary, and the development of a didactic sequence with the application of the terrarium. Based on the data production instruments, the results were evaluated through content analysis, in which four categories were created for thematic analysis: concepts explored and the degree of influence of continuing education in Critical Environmental Education in the view of participating teachers; science teaching in early childhood education; knowledge and use of the didactic sequence and the terrarium as pedagogical practices; and knowledge and existence of socioenvironmental projects included in the schools’ Political-Pedagogical Project. It was possible to observe the need for specific continuing education in Critical Environmental Education for teachers and that the practical experiment with the terrarium helped stimulate and understand content related to concepts and theories to guide children in Early Childhood Education in favor of Critical Environmental Education and Scientific Literacy, contributing to the development of critical thinking and environmental awareness.